2010
DOI: 10.1242/jcs.068445
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of synapsin I by Src regulates synaptic-vesicle trafficking

Abstract: SummarySynapsins are synaptic vesicle (SV)-associated phosphoproteins involved in the regulation of neurotransmitter release. Synapsins reversibly tether SVs to the cytoskeleton and their phosphorylation by serine/threonine kinases increases SV availability for exocytosis by impairing their association with SVs and/or actin. We recently showed that synapsin I, through SH3-or SH2-mediated interactions, activates Src and is phosphorylated by the same kinase at Tyr301. Here, we demonstrate that, in contrast to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 59 publications
(82 reference statements)
2
30
0
Order By: Relevance
“…The observation that deletion of PKA/CaMK phosphorylation sites did not mimic the effect of SynI deletion in a fraction of the tested neurons suggests that alternative activity-dependent signaling pathways impinging on SynI, such as those mediated by the kinases Src and CDK5 (Kim and Ryan, 2010;Messa et al, 2010), may be involved in causing the increase in RRP size associated with PTP. Alternative pathways have been described in Helix neurons or in the calyx of Held synapse, where MAPK or myosin light chain kinase was found to be involved in regulating SV availability via cross talk with other Ca 2ϩ -dependent pathways (Lee et al, 2008;Giachello et al, 2010).…”
Section: Pka/camk Phosphorylation Of Syni Mediates the Rrp Increase Imentioning
confidence: 97%
“…The observation that deletion of PKA/CaMK phosphorylation sites did not mimic the effect of SynI deletion in a fraction of the tested neurons suggests that alternative activity-dependent signaling pathways impinging on SynI, such as those mediated by the kinases Src and CDK5 (Kim and Ryan, 2010;Messa et al, 2010), may be involved in causing the increase in RRP size associated with PTP. Alternative pathways have been described in Helix neurons or in the calyx of Held synapse, where MAPK or myosin light chain kinase was found to be involved in regulating SV availability via cross talk with other Ca 2ϩ -dependent pathways (Lee et al, 2008;Giachello et al, 2010).…”
Section: Pka/camk Phosphorylation Of Syni Mediates the Rrp Increase Imentioning
confidence: 97%
“…Studies using specific Src inhibitors have indicated that Src family kinases directly modulate neurotransmitter release by interfering with activity-dependent Ca 2+ entry, actin dynamics and exocytosis (Ohnishi et al, 2001;Baldwin et al, 2006;Cheng et al, 2007, but see Wang, 2003Shyu et al, 2005). One of the mechanisms suggested for Src regulation of neurotransmitter release is by modifying, through phosphorylation, the activity of proteins, such as the synapsins, involved in the regulation of exocytosis and synaptic vesicles trafficking (Messa et al, 2010;Bykhovskaia, 2011).…”
Section: Mechanism Of Action Of the N-terminal And C-terminal Tyrosinmentioning
confidence: 99%
“…Similarly, differential phosphorylation of the synaptic vesicle protein Synapsin has been implicated in modulating its various roles including neurotransmitter release, vesicle clustering, maintaining the reserve pool, and vesicle delivery to the active zones. These processes are regulated via a dynamic phosphoregulation cycle which involves multiple phosphorylation sites and several kinases including cAMP-dependent protein kinase A, PKA (at site 1 (Ser9)) (Angers, et al, 2002;Menegon, et al, 2006), Ca2+/calmodulin-dependent kinase CaMKII and VI (at sites 1, 2 andand 7 (ser62, Ser67 and Ser549 and Ser551)) (Chi, et al, 2003;Giachello, et al, 2010), and tyrosine kinase Src (site 8 (Tyr301)) (Messa, et al, 2010). Phosphorylation on serine residues upon activation of PKA, CaMK and MAPK signaling pathways, promotes the dissociation of Synapsin from synaptic vesicles and/or the actin network which results in trafficking of synaptic vesicles from the reserve pool to the ready releasable pool for exocytosis (Chi, et al, 2003;Giachello, et al, 2010;Menegon, et al, 2006).…”
Section: Multiple Phosphorylation Sites Modulated By Single or Multipmentioning
confidence: 99%
“…Phosphorylation on serine residues upon activation of PKA, CaMK and MAPK signaling pathways, promotes the dissociation of Synapsin from synaptic vesicles and/or the actin network which results in trafficking of synaptic vesicles from the reserve pool to the ready releasable pool for exocytosis (Chi, et al, 2003;Giachello, et al, 2010;Menegon, et al, 2006). In contrast, Src kinase-mediated phosphorylation of Synapsin enhances its oligomerization and increases its association with synaptic vesicles and the cytoskeleton, stimulating the re-clustering of recycled vesicles and subsequent recruitment to the reserve pool (Messa, et al, 2010). In addition, phosphorylation at different Synapsin sites can occur concurrently through the selectivity of kinase/phosphatase activation, which is dependant on the stimulus and the signaling pathways implicated.…”
Section: Multiple Phosphorylation Sites Modulated By Single or Multipmentioning
confidence: 99%